Estimación de la manutención infantil para hogares monoparentales en las ciudades capitales de Bolivia - Edison Choque; Carla Salamanca; Isabel Quehui (Institute for Advanced Development Studies (INESAD), 2021)
– This study proposes a methodology for estimating child support, which combines two approaches. The first corresponds to the marginal approach, which approximates the cost of the child maintenance by comparing an equivalent income from households with the same level of well-being. The second is the per capita - average approach that approximates this cost through the so-called exclusive spending. We use the 2015-2016 Family Budget Survey to estimate the maintenance, considering households in five capital cities and the metropolis area of La Paz, which are above the moderate poverty line in Bolivia. Results shows that, on average, monthly child support represents 67% and 97% of the national minimum wage when the child studies in a public and private school, respectively. In this regard, we evidence that these percentages are higher than the minimum of 20% established by the Family and Family Process Code.
Keywords: D1; D11; D12; 330; Matching; child support; single parent home; common rank